Hydrogel arrays formed via differential wettability patterning enable combinatorial screening of stem cell behavior. (1st April 2016) - Le, Ngoc Nhi T.; Zorn, Stefan; Schmitt, Samantha K.; Gopalan, Padma; Murphy, William L.
Graphical abstract: Abstract: Here, we have developed a novel method for forming hydrogel arrays using surfaces patterned with differential wettability. Our method for benchtop array formation is suitable for enhanced-throughput, combinatorial screening of biochemical and biophysical cues from chemically defined cell culture substrates. We demonstrated the ability to generate these arrays without the need for liquid handling systems and screened the combinatorial effects of substrate stiffness and immobilized cell adhesion peptide concentration on human mesenchymal stem cell (hMSC) behavior during short-term 2-dimensional cell culture. Regardless of substrate stiffness, hMSC initial cell attachment, spreading, and proliferation were linearly correlated with immobilized CRGDS peptide concentration. Increasing substrate stiffness also resulted in increased hMSC initial cell attachment, spreading, and proliferation; however, examination of the combinatorial effects of CRGDS peptide concentration and substrate stiffness revealed potential interplay between these distinct substrate signals. Maximal hMSC proliferation seen on substrates with either high stiffness or high CRGDS peptide concentration suggests that some baseline level of cytoskeletal tension was required for hMSC proliferation on hydrogel substrates and that multiple substrate signals could be engineered to work in synergy to promote mechanosensing and regulate cell behavior. Statement of significance: Our novel array formation method using surfaces patterned with differential wettability offers the advantages of benchtop array formation for 2-dimensional cell cultures and enhanced-throughput screening without the need for liquid handling systems. Hydrogel arrays formed via our method are suitable for screening the influence of chemical (e.g. cell adhesive ligands) and physical (stiffness, size, shape, and thickness) substrate properties on stem cell behavior. The arrays are also fully compatible with commercially available micro-array add-on systems, which allows for simultaneous control of the insoluble and soluble cell culture environment. This study used hydrogel arrays to demonstrate that synergy between cell adhesion and mechanosensing can be used to regulate hMSC behavior.